Teachers Strategies in Teaching English Vocabulary in Junior High School - Rodolfo Josafat Gultom; Jesie Nuari Simarmata; Olin Risnawati Purba; Erikson Saragih (Journal of English Language and Education, 2022)
This study aims to describe the strategies used by teachers and the problems teachers deal with in teaching vocabulary.  The author uses qualitative description to analyze the data. Data were extracted from questionnaires and documents. The object of this study is the process of teaching vocabulary to university students.  Based on the results of the questionnaires and documents, the author draws some conclusions about the teacher's strategy and the problems that the teacher has solved. The strategies teachers use are: (1) using a translation, (2) a game, (3) using a dictionary, and (4) a story. The problems the teacher deals with are (1) the teacher calls, noisy students, and questions the materials or orders noisy students to leave, (2) the teacher gives advice and motivation about the importance of learning English and the importance of improving vocabulary. In addition, teachers also apply another strategy by giving grades to active students. Students can also review difficult materials with the teacher outside of the classroom, (3) the teacher provides new vocabulary written on the board at each meeting to improve vocabulary. The strategy used by the teacher is good because the strategy can make the students more active. In addition, strategies used by teachers can encourage student participation in the classroom.